2005
DOI: 10.1051/0004-6361:20052794
|View full text |Cite
|
Sign up to set email alerts
|

Footpoint excitation of standing acoustic waves in coronal loops

Abstract: Abstract.A new theoretical model for the study of slow standing sausage mode oscillations in hot (T > 6 MK) active region coronal loops is presented. These oscillations are observed by the SUMER spectrometer on board the SoHO satellite. The model contains the transition region and the upper chromosphere which enables us to study the entire process of hot loop oscillationsfrom the impulsive footpoint excitation phase to the rapid damping phase. It is shown that standing acoustic waves can be excited by an impul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 30 publications
6
59
0
Order By: Relevance
“…Recently, the high-resolution observation with the Atmospheric Imaging Assembly (AIA Lemen et al 2012) onboard the Solar Dynamics Observatory (SDO, Pesnell et al 2012), evidenced that oscillations in the hot coronal loops are excited by an energy release at one of the footpoints of the arcade loops (Kumar et al 2013(Kumar et al , 2015. These observational findings are consistent with the interpretation of SUMER oscillations in terms of slow magnetoacoustic waves (Ofman & Wang 2002;Nakariakov et al 2004;Taroyan et al 2005).…”
Section: Introductionsupporting
confidence: 91%
“…Recently, the high-resolution observation with the Atmospheric Imaging Assembly (AIA Lemen et al 2012) onboard the Solar Dynamics Observatory (SDO, Pesnell et al 2012), evidenced that oscillations in the hot coronal loops are excited by an energy release at one of the footpoints of the arcade loops (Kumar et al 2013(Kumar et al , 2015. These observational findings are consistent with the interpretation of SUMER oscillations in terms of slow magnetoacoustic waves (Ofman & Wang 2002;Nakariakov et al 2004;Taroyan et al 2005).…”
Section: Introductionsupporting
confidence: 91%
“…Tirry & Poedts (1998) studied the heating of 2D coronal arcades by linear resonant Alfvén waves that are excited directly by photospheric toroidally polarised footpoint motions. Taroyan et al (2005) studied the excitation of slow standing waves in a 1D loop by footpoint heat deposition. They found that the time profile of the longlasting pulse determines whether a standing or propagating wave is excited.…”
Section: Introductionmentioning
confidence: 99%
“…These oscillations have a phase shift of about one-quarter period between velocity and intensity. The periods and damping times of the standing slow waves are in the ranges of 8.6-32.3 min and 3.1-42.3 min, respectively Wang et al, 2002aWang et al, , 2002bWang et al, , 2003Wang et al, , 2005Banerjee et al, 2007;Erdélyi et al, 2008). The effect of energy dissipation on the slow waves through thermal conduction, compressive viscosity, radiative cooling, and heating on the periods, period ratio, and damping times has formed the focus of recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Only with the combined effect of thermal conduction and viscosity the results are consistent with the observations. Moreover, Taroyan et al (2005) investigated the effect of temperature inhomogeneity on the dissipation of standing slow waves through considering thermal conduction and optically thin radiative losses. They found that the damping time of the isothermal loops is proportional to the wave period and the oscillations are rapidly damped mainly by thermal conduction.…”
Section: Introductionmentioning
confidence: 99%